Estudo do comportamento da mec??nica vascular no processo de descelulariza????o pulmonar - Palma, Renata Kelly da (2015)
Organ biofabrication is a potential future alternative for obtaining viable organs for transplantation. Achieving intact scaffolds to be recellularized is a key step in lung bioengineering. The decellularizing agent perfusion technique via the pulmonary artery (PA) has been shown very effective in the process however; vascular perfusion pressure and flow vary along the pulmonary decellularization process. These factors are not fully understood it being very important in the optimization process, ensuring the integrity of the scaffold. The objectives were to characterize the pressure / pulmonary vascular flow associated with variation in vascular resistance (VR), according to the control of the infusion (pressure or flow) at the time of the infusion of different decellularizing agents in PA and determine the VR's behavior in relation to different pressures of lung inflation (tracheal pressure) and perfusion (pulmonary artery). For the first study, were used 43 lungs of the healthy mice (C57/BL6) with 7???8 weeks old and in the second study, lungs of the 5 healthy rat (Sprague- Dawley) with 7-8 weeks old. In the first study, after excision and tracheal cannulation, lungs were inflated at 10 cmH2O airway pressure and subjected to conventional decellularization process being perfused through PA. For the second study, the decellularized lungs were subjected to variations in tracheal pressure (0 to 15 cmH2O) and vascular pressure (5 to 30 cmH2O). Pressure (PPA) and flow (V???PA) at the pulmonary artery were continuously measured. The VR (VR=PPA/V???PA) considerably varied throughout lung decellularization, particularly for pressure controlled perfusion, as compared with flow-controlled perfusion. This study shows that monitoring perfusion mechanics throughout decellularization provides information relevant for optimizing the process time while ensuring that vascular pressure is kept within a safety range to preserve the organ scaffold integrity. Moreover, arterial lung pressure has more influence on behavior of vascular resistance in decellularized lungs than positive airway pressure, providing information that could be relevant for future cell repopulation by using the vascular resistance as a facilitator cell distribution throughout pulmonary circuit.